Precautions for seafood consumers: An updated review of toxicity, bioaccumulation, and rapid detection methods of marine biotoxins - Yifan Wang; Ansar Javeed; Cuiqin Jian; Qiuyu Zeng; Bingnan Han (Ecotoxicology and Environmental Safety, 2024)
Seafood products are globally consumed, and there is an increasing demand for the quality and safety of these products among consumers. Some seafoods are easily contaminated by marine biotoxins in natural environments or cultured farming processes. When humans ingest different toxins accumulated in seafood, they may exhibit different poisoning symptoms. According to the investigations, marine toxins produced by harmful algal blooms and various other marine organisms mainly accumulate in the body organs such as liver and digestive tract of seafood animals. Several regions around the world have reported incidents of seafood poisoning by biotoxins, posing a threat to human health. Thus, most countries have legislated to specify the permissible levels of these biotoxins in seafood. Therefore, it is necessary for seafood producers and suppliers to conduct necessary testing of toxins in seafood before and after harvesting to prohibit excessive toxins containing seafood from entering the market, which therefore can reduce the occurrence of seafood poisoning incidents. In recent years, some technologies which can quickly, conveniently, and sensitively detect biological toxins in seafood, have been developed and validated, these technologies have the potential to help seafood producers, suppliers and regulatory authorities. This article reviews the seafood toxins sources and types, mechanism of action and bioaccumulation of marine toxins, as well as legislation and rapid detection technologies for biotoxins in seafood for official and fishermen supervision.